DEVELOPING PROFESSIONAL COMMUNICATIVE COMPETENCE OF TOURISM MAJORS THROUGH ENGLISH FOR SPECIFIC PURPOSES (ESP) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article explores the development of professional communicative competence of tourism majors through English for Specific Purposes (ESP). In the context of the rapidly evolving tourism industry, effective professional communication in English has become a core requirement for future specialists. The study focuses on ESP as a methodological framework that integrates linguistic, professional, and communicative components of language education. Particular attention is given to profession-oriented discourse, functional language use, and situational communication relevant to tourism contexts. The article analyzes how ESP-based instruction supports the development of speaking, interactional strategies, and professional pragmatics required in real workplace settings. Additionally, the role of needs analysis and profession-specific tasks is examined as a means of aligning language instruction with industry demands. The findings suggest that ESP-based English instruction significantly enhances tourism students’ readiness for professional communication and contributes to the systematic formation of professional communicative competence.